Primary intravascular large B-cell lymphoma of pituitary - K R Anila; Rekha A Nair; Sumod M Koshy; Priya M Jacob (Wolters Kluwer Medknow Publications, 2012)
A 68-year-old retired nurse, who was a known hypertensive on medication, presented with prolonged fever of 2-month duration without any clinical evidence of infection. On examination she had altered mental status. She also had other nonspecific complaints such as sleep disturbances, loss of weight, etc. On investigation, she was found to have anemia, thrombocytopenia, raised erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and lactate dehydrogenase (LDH) values. She also had electrolyte imbalance. Radiological evaluation of brain showed mass lesion in the sella turcica, suggestive of pituitary adenoma. Biochemical evaluation showed hypopituitarism. Trans-sphenoidal biopsy was done. Based on histopathological and immunohistochemical findings a diagnosis of intravascular large B-cell lymphoma (IVLBCL) of pituitary was made. Our patient's condition deteriorated rapidly and she succumbed to her illness before therapy could be initiated. We are reporting this case because of the rare subtype of large B-cell lymphoma presenting at an extremely unusual primary site.